1999
DOI: 10.1063/1.477877
|View full text |Cite
|
Sign up to set email alerts
|

High density adsorbed oxygen on Rh(111) and enhanced routes to metallic oxidation using atomic oxygen

Abstract: Physical and chemical properties of high density atomic oxygen overlayers under ultrahigh vacuum conditions: (1×1)-O/Rh (111)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 27 publications
5
51
0
Order By: Relevance
“…The 'oval' protrusions are observed in the Cu(110)-c(6Â2)-8O phase [48] and the 'honeycomb' protrusions composed of the 'dumbbells' are observed from the Cu(111)-O surface at higher temperature [49]. All the (Ag, Cu, Ni, Pt)(110) [53,54] and Ru(0001)-O surfaces [55,56]. STM studies should be able to reveal inherently common features caused by oxygen adsorption from all these many specific forms.…”
Section: Alternation Of Atomic Valenciesmentioning
confidence: 92%
See 2 more Smart Citations
“…The 'oval' protrusions are observed in the Cu(110)-c(6Â2)-8O phase [48] and the 'honeycomb' protrusions composed of the 'dumbbells' are observed from the Cu(111)-O surface at higher temperature [49]. All the (Ag, Cu, Ni, Pt)(110) [53,54] and Ru(0001)-O surfaces [55,56]. STM studies should be able to reveal inherently common features caused by oxygen adsorption from all these many specific forms.…”
Section: Alternation Of Atomic Valenciesmentioning
confidence: 92%
“…The former presents zigzag strips, while the latter gives a regular array of depressions and protrusions. One may attribute such a difference to the Á values in Figs [53]. Common to all other O-chemisorbed systems, the first layer spacing expands and the second contracts.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these steps, i.e. the chemisorption of oxygen on Rh single crystal surfaces, has been the subject of intensive experimental and theoretical research, [7][8][9][10] but only few experimental studies have addressed the ensuing formation of sub-surface oxygen, [11][12][13][14][15][16][17] . In one of these studies it could recently be shown 16 that exposure of the Rh(111) surface to O 2 at moderatly elevated temperatures (∼ 470 K) leads to the formation of sub-surface oxygen species, and there is evidence that at least ∼ 0.9 monolayer (ML) of O is adsorbed on the surface before sub-surface sites are occupied.…”
Section: Introductionmentioning
confidence: 99%
“…oxygen incorporation will only start after completion of a full O(1 × 1) overlayer, in nice agreement with experimental findings. 26,27 Close to Θ = 1 ML the energy differences are very small in the case of Rh though. Hence, a fi-…”
Section: B Oxygen Accommodation Below the Top Metal Layermentioning
confidence: 99%